An Analysis of United Kingdom Inflows and Outflows of Direct Foreign Investment - Boatwright, B. D.; Renton, G. A. (The Review of Economics and Statistics, 1975)
A substantial portion of the United Kingdom's .11.international transactions in long-term capital is comprised of inflows and outflows of direct investment in foreign subsidiaries and branches, whether by acquisition of share and loan capital, retention of profits, changes in branch indebtedness, or by changes in intercompany accounts. These transactions have historically been very large. On average, since 1961 U. K. firms have invested abroad in direct investments about 11.5%o as much as they have invested at home. On a per capita basis, the U. K. is one of the world's largest foreign investors. These flows are of considerable importance for the balance of payments. The quarterly value of the deficit on direct investment account has averaged ?28 million since 1961, compared with an average surplus on current account of ?34 million, and the variance of the balance on direct investment is about 1 1% of the variance of the balance on current account. Section II describes a model of direct investment flows. This model is tested in section III. The final section assesses some of the implications of the estimated model.